Phenanthroline-Catalyzed Stereoretentive Glycosylations - Yu, Fei (Angew Chem Int Ed Engl, 2019)
Carbohydrates are essential moieties of many bioactive molecules in nature. However, efforts to elucidate their modes of action are often impeded by limitations in synthetic access to well-defined oligosaccharides. Most of the current methods rely on the design of specialized coupling partners to control selectivity during formation of glycosidic bonds. Herein, we report a commercially available phenanthroline to catalyze stereoretentive glycosylation with glycosyl bromides. The method provides efficient access to α−1,2-cis glycosides. This protocol has been performed for the large-scale synthesis of an octasaccharide adjuvant. Density functional theory calculations, together with kinetic studies, suggest that the reaction proceeds via double S(N)2 mechanism.